A mathematical model for investigating the effect of reaction temperature and hydrogen amount on the catalyst yield during propylene polymerization - Varshouee, Gholam Hossain (Array, 2019)
In this study, the effect of reaction temperature and hydrogen amount, as the most effective process variables on the Ziegler-Natta catalysts yield during propylene polymerization, was investigated with the aid of a validated mathematical model. The approach applied in this modelling was the polymer moment balance technique (population balance approach) derived from the statistics expected value. The model was coded in MATLAB® & Simulink®, and then validated by experimental data coming from a laboratory-scale reactor. The main target of this study was to gain considerable insight into Ziegler-Natta catalyst performance against variables change. The model might be applicable for catalyst makers to evaluate and improve their catalysts, and could also be useful for process chemical engineers to easily operate the plant, replace new catalyst, optimise process conditions, generate new formulation for a new grade, and use maximum catalytic potential. Accordingly, the model could be applied in basic and applied research in this field.